2019
DOI: 10.1016/j.matdes.2018.107565
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical properties of amorphous metallic tungsten-oxygen and tungsten-oxide coatings

Abstract: Metallic amorphous tungsten-oxygen and amorphous tungsten-oxide films, deposited by Pulsed Laser Deposition, are characterized. The correlation is investigated between morphology, composition, and structure, measured by various techniques, and the mechanical properties, characterized by Brillouin Spectroscopy and the substrate curvature method. The stiffness of the films is correlated to the oxygen content and the mass density. The elastic moduli decrease as the mass density decreases and the oxygen-tungsten r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
3
10
0
Order By: Relevance
“…The Raman spectra for both the as-synthesized samples and the samples annealed at 100 °C do not show any peaks, indicating that the porous films are amorphous, which is in accordance with the XRD results. These characteristic lines in Raman spectra have been reported earlier in [53], where authors observed Raman peaks only when samples were annealed above 400 °C.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The Raman spectra for both the as-synthesized samples and the samples annealed at 100 °C do not show any peaks, indicating that the porous films are amorphous, which is in accordance with the XRD results. These characteristic lines in Raman spectra have been reported earlier in [53], where authors observed Raman peaks only when samples were annealed above 400 °C.…”
Section: Resultssupporting
confidence: 84%
“…The slight shift towards lower wavenumbers of peaks at 272 and 719 cm −1 could be due to the growth occurring in a non-equilibrium process, so the synthesized films are obtained with high stress (compressive or tensile) mainly because of the gradient temperature between filament and substrate. This shift can also be attributed to the increment in the particle size [53,61,62].…”
Section: Resultsmentioning
confidence: 99%
“…According to [70], tungsten oxides with O content higher than ≈73 % behaves as a dielectrics whereas for concentrations lower than 73 % the sample behaves as a metal. According to [71], tungsten nitrides are good absorbers but with k values which can be ≈ 60% lower than the corresponding value for tungsten.…”
Section: Information Retrieved From Raman Absolute Band Intensitiesmentioning
confidence: 99%
“…The combination of the techniques gave access to a wide range of frequencies, allowing detailed determination of the elastic properties of the film [113]. Brillouin spectroscopy turned out to be a useful characterization tool also for other types of films of interest in materials science, like boron films [114] and amorphous and nanocrystalline tungsten films [115].…”
Section: Brillouin Spectroscopymentioning
confidence: 99%